Thromboprophylaxis for orthopedic surgery; An updated meta-analysis. Issue 199 (March 2021) - Haykal, Tarek; Adam, Soheir; Bala, Areeg; Zayed, Yazan; Deliwala, Smit; Kerbage, Josiane; Ponnapalli, Anoosha; Malladi, Srikanth; Samji, Varun; Ortel, Thomas L.
Abstract: Background: Venous thromboembolism (VTE) is a serious complication of orthopedic surgery. Low molecular weight heparin (LMWH) has been the standard of care for thromboprophylaxis in this population. However, direct oral anticoagulants (DOACs) are increasingly being used as alternatives. Objective: To assess the efficacy and safety of DOACs versus LMWH for thromboprophylaxis in orthopedic surgery. Methods: We searched MEDLINE, Embase, and the Cochrane Collaboration Central Register of Controlled Trials from inception until April 2020, for randomized controlled trials (RCTs) comparing DOACs with LMWH for thromboprophylaxis in orthopedic surgery. Results: Twenty-five RCTs met inclusion criteria, including 40, 438 patients, with a mean age of 68 years and 50% were males. Compared to LMWH, DOACs were associated with a significant reduction of major VTE; defined as the composite events of proximal deep vein thrombosis (DVT), pulmonary embolism (PE), and VTE-related mortality (RR 0.33; 95% CI: 0.20–0.53; P <0.01), and total DVT (RR: 0.59; 95% CI: 0.48–0.73; P<0.01), but not PE (RR 0.81; 95% CI: 0.49–1.34; P =0.42). There was no statistically significant difference between both groups on the incidence of major bleeding (RR 0.99; 95% CI: 0.77–1.27; P =0.92), clinically relevant non-major bleeding (RR 1.04; 95% CI: 0.92–1.17; P =0.52), all-cause mortality (RR 1.06; 95% CI: 0.64–1.76; P =0.83), VTE-related mortality (RR 0.84; 95% CI: 0.40–1.74; P =0.64) and bleeding-related mortality (RR 1.24; 95% CI: 0.30–5.18; P =0.77). Conclusion: For patients undergoing orthopedic surgery, thromboprophylaxis with DOACs is associated with a significant reduction of major VTE and DVT, compared to LMWH. Safety outcomes were not significantly different between both treatment groups. Graphical abstract: Unlabelled Image Highlights: Patients undergoing total knee arthroplasty and total hip arthroplasty are at risk for venous thromboembolism. Surgical thromboprophylaxis with DOACs was associated with a significant reduction in rates of VTE, compared to LMWH. Major bleeding and all-cause mortality were not significantly different in both treatment groups.